Governance and compliance in accounting education in Vietnam – case of a public university. (4th May 2017) - Bui, Binh; Hoang, Hien; Phan, Duc P. T.; Yapa, P. W. Senarath
ABSTRACT: Prior research suggests that despite the mass development of higher education in Vietnam recently, the quality of higher education is declining. This study aims to understand the impact of the education reform on the quality of university accounting education by investigating the involvement of different stakeholders in accounting education within one leading university in Vietnam. The findings from the interviews of key stakeholders suggest that accounting education in Vietnam is driven by reduced state control, growing institutional autonomy and increasing external guidance. This has come at the expense of reduced academic self-governance as lecturers have discretion in curriculum delivery at the individual course level, but little input into the decision-making at the school or university level and minimal participation in the curriculum development process. The findings enable regulators and decision-makers to better understand the dynamics between stakeholders in accounting education to enhance accounting graduates' competencies and outcomes.